2008
DOI: 10.1097/mca.0b013e3282f3fbef
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of subclinical atherosclerosis in asymptomatic diabetic patients by 64-slice computed tomography

Abstract: Our results show that the prevalence of coronary plaques detectable by 64-slice CT in asymptomatic diabetic patients is very high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 38 publications
5
23
0
2
Order By: Relevance
“…Two studies compared asymptomatic patients with and without DM. 20,21 The prevalence of coronary plaques ranged from 80% to 93% and significant coronary stenosis was higher in diabetics than in a control group. Scholte et al 22 found that 41% of the plaques were non-calcified, meaning they would not have been detected by coronary artery calcium imaging, while Raggi et al 23 showed that 40% of diabetics have coronary artery calcification.…”
Section: Introductionmentioning
confidence: 97%
“…Two studies compared asymptomatic patients with and without DM. 20,21 The prevalence of coronary plaques ranged from 80% to 93% and significant coronary stenosis was higher in diabetics than in a control group. Scholte et al 22 found that 41% of the plaques were non-calcified, meaning they would not have been detected by coronary artery calcium imaging, while Raggi et al 23 showed that 40% of diabetics have coronary artery calcification.…”
Section: Introductionmentioning
confidence: 97%
“…18,19 Using MDCT, Iwasaki et al identified CAD in 33.3% of asymptomatic diabetic patients, but that study lacked follow-up and functional evaluation of stenotic lesions. 18 Third, the incidence of cardiac events increased as coronary artery calcium score (CACS) increased. CACS has been reported to predict all-cause mortality and cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies compared asymptomatic patients with and without DM. 6,7 The prevalence of coronary plaques ranged from 80% to 93% and significant coronary stenosis (range 29%-33%) was significantly higher in patients with DM than in a control population (range 7%-16%). In one study, 41% of the plaques were non-calcified 8 meaning they would not have been detected by CAC imaging.…”
Section: Coronary Computed Tomography Angiographymentioning
confidence: 97%